PENGARUH PENGGUNAAN MORDAN ASAM JAWA (Tamarindus Indica Linn) DAN ASAM KANDIS (Garcinia Parvifolia Miq) TERHADAP HASIL PENCELUPAN BAHAN SUTERA DENGAN MENGGUNAKAN EKSTRAK DAUN ANDONG (Cordyline Fruticosa L. A. Cheval) - Almagita, Rachmy Bunga; Novrita, Sri Zulfia; Nelmira, Weni (Journal of Home Economics and Tourism, 2017)
This study aimed to describe the name of a color (hue), dark-light color (value), the flatness of color, and differences in light and dark and the flatness of the color of the effect of the mordant tamarind and sour kandis the results of dyeing silk using leaf extract Andong (Cordyline fruticosa LA Cheval). This research is an experimental research. This type of data is a primary data sourced from the 13 panelists. The object is dipped silk fabric with leaf extract carriage with tamarind and sour kandis. Where the data analysis was performed using ANOVA and percentage. From the results of dyeing without mordant produce color Gray (64% white) with a value of less light and color average flat. While the dyeing with mordant tamarind produce color Warm Brown with a value reasonably bright and color average flat and dyeing with mordant sour kandis produce color Off-White Snow with the value of light and color average flat. The results of hypothesis testing data obtained for light and dark colors (value) is Fcount> Ftable = 4.212> 3.26 means that there are significant differences. As for the flatness of color data obtained is Fcount> Ftable = 1.874 â‰¤ 3.26 means that there are no significant differences. Keywords: Effect Mordant, Leaf Extract Andong